PERSPEKTIF GENDER DALAM KEBERLANJUTAN SAWIT - Rini Hanifa; Eusebius Pantja Pramudya (Masyarakat Indonesia, 2017)
The emerging initiatives to improve sustainability of the palm oil sector, i.e. RSPO and ISPO, have started paying attention to gender aspect. This study analyzes the ways the sustainable palm oil initiatives have addressed gender issues. The analysis is based on literature study and field information from Riau, Jambi, North Sumatra, and East Kalimantan. The findings of this study indicate that several initiatives to achieve gender equality in sustainable palm oil have not successfully reach its objective because of the limitations in operationalizing gender perspectives into sustainability standards. Gender issue in the standards is still limited to women’s protection from the occupational risks of working in the palm oil sector, which is still within the scope of Women in Development  paradigm. Further development is needed by applying Gender and Development paradigm to achieve equitable gender relations between men and women and addressing structural barriers that influence them is still limited.Keyword: sustainable palm oil, RSPO, ISPO, gender perspective ABSTRAKBerbagai inisiatif untuk meningkatkan keberlanjutan (sustainability) sektor sawit yang belakangan muncul, seperti RSPO dan ISPO, mulai ikut memberikan perhatian terhadap aspek gender. Studi ini mencoba menganalisis bagaimana inisiatif-inisiatif sawit berkelanjutan berusaha menjawab isu gender. Analisis dilakukan dengan berdasarkan pada studi pustaka dan informasi lapangan dari Riau, Jambi, Sumatra Utara, dan Kalimantan Timur. Temuan dari penelitian ini menunjukkan upaya membangun kesetaraan gender dalam sawit berkelanjutan belum terjadi sepenuhnya karena keterbatasan dalam mengoperasionalkan perspektif gender dalam standar sustainability. Isu gender yang dicakup masih sebatas upaya perlindungan perempuan terhadap risiko pekerjaan dalam sektor sawit, yang masih sebatas paradigma women in development. Pengembangan yang seharusnya dilakukan adalah mengaplikasikan paradigma gender and development untuk mencapai relasi yang setara antara laki-laki dan perempuan serta mengatasi berbagai hambatan struktural yang memengaruhinya.Kata Kunci: perspektif gender, keberlanjutan sawit, RSPO, ISPO